1994
DOI: 10.1093/ajcn/59.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactation on resting metabolic rate and on diet- and work-induced thermogenesis

Abstract: Energy metabolism was measured in 24 women before pregnancy and during lactation (2 mo postpartum). Resting metabolic rate (RMR) increased by 0.17 +/- 0.38 kJ/min and postprandial metabolic rate (PPMR) showed a similar increase (0.17 +/- 0.45 kJ/min). Thus, the thermic effect of the meal (PPMR minus RMR) was not affected by lactation. Between subjects, the lactation-induced increase in RMR appeared to be positively related to body weight. During lactation gross metabolic rates during cycling (CMR) were slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…RMR has been previously shown to increase in animals exposed to cold or in females during peak lactation (Garton et al, 1994;Spaaij et al, 1994;Speakman and McQueenie, 1996;Johnson et al, 2001b). In the present study, an increase in RMR in female hamsters lactating at 5°C was observed.…”
Section: -J Zhaomentioning
confidence: 95%
“…RMR has been previously shown to increase in animals exposed to cold or in females during peak lactation (Garton et al, 1994;Spaaij et al, 1994;Speakman and McQueenie, 1996;Johnson et al, 2001b). In the present study, an increase in RMR in female hamsters lactating at 5°C was observed.…”
Section: -J Zhaomentioning
confidence: 95%
“…While the subjects in the present study were nutritionally normal, their nutritional history was different. The average combined heights of the two group (155.8 AE 6.3 cm) was about the 10th percentile of the U.S. National Center for Health Statistics data (Frisancho, 1993) and signi®cantly less (P0 .001) than the height of the subjects studied by Spaaij et al (1994). This is no doubt a re¯ection of the marginal malnutrition during growth which is common in this socioeconomic group in Cali (Spurr & Reina, 1989).…”
Section: Discussionmentioning
confidence: 74%
“…Increased metabolic ef®ciency during lactation has been reported in dairy cattle (Moe, 1981) and rats (Roberts & Coward, 1984), but there is less evidence for such a change in humans. Postprandial thermogenesis in lactating women was reduced by 30% in one study (Illingworth et al, 1986), but was unchanged in others (Spaaij et al, 1994;Piers et al, 1995).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The first study to estimate pup rearing costs in sea otters suggested that female energy demands reach twice prepartum levels by the time a pup nears weaning (Thometz et al, 2014); however, this study only examined the metabolic needs of pups and could not account for the energetic cost of milk production. In general, terrestrial mammals exhibit increased resting metabolic rate (RMR) during lactation, although the extent and duration of this increase are highly variable among species (Brockway et al, 1963;Fleming et al, 1981;Garton et al, 1994;Hammond and Diamond, 1992;Harder et al, 1996;Król et al, 2003;Poppitt et al, 1994;Prentice et al, 1989;Spaaij et al, 1994;Speakman and Mcqueenie, 1996;Stephenson and Racey, 1993a,b;Thompson and Nicoll, 1986). In contrast, the cost of milk production in marine mammals appears minimal in the species studied to date (Antarctic and Galapagos fur seals: Costa and Trillmich, 1988; Northern elephant seals: Costa et al, 1986; California sea lions: Williams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%